CD8+CD122+ T-Cells: A Newly Emerging Regulator with Central Memory Cell Phenotypes - Liu, Junfeng; Chen, Dacan; Nie, Golay D.; Dai, Zhenhua (Frontiers in Immunology, 2015)
CD8+CD122+ T-cells have been traditionally described as antigen-specific memory T-cells that respond to previously encountered antigens more quickly and vigorously than their naïve counterparts. However, mounting evidence has demonstrated that murine CD8+CD122+ T-cells exhibit a central memory phenotype (CD44highCD62Lhigh), regulate T cell homeostasis, and act as regulatory T-cells (Treg) by suppressing both autoimmune and alloimmune responses. Importantly, naturally occurring murine CD8+CD122+ Tregs are more potent in immunosuppression than their CD4+CD25+ counterparts. They appear to be acting in an antigen-nonspecific manner. Human CD8+CXCR3+ T-cells are the equivalent of murine CD8+CD122+ Tregs and also exhibit central memory phenotypes. In this mini-review article, we will summarize recent progresses in their phenotypes, homeostatic expansion, antigen-specificity, roles in the suppression of alloimmune and autoimmune responses, and the mechanisms underlying their inhibitory function.